Antibiotic-resistant bacteria in water and fish: A risk to human health - Zaky, Mahmoud M. M; Toubar, Saly M. E; El-Shafey, Ahmed Samy (International journal of celiac disease, 2021)
Water pollution is one of the most severe environmental problems that affect public health and can cause diseases as gastrointestinal diseases. Microbial pollution of Lake Manzala was studied in four main localities, Kapoty, Bashtier, Mataryia and Gamil areas which receive a high load of sewage, agricultural and industrial wastes from different sources. A total of 50 bacterial isolates from water and fish were identified using API 20E system, revealed that 20% of these bacterial strains, were related to Escherichia coli (E. coli), which has been subjected to different antibiotics, such as Ampicillin, Penicillin G, Streptomycin, tetracycline, Gentamycin, Chloramphenicol, rifampicin and Cefotaxime. All strains variation of resistance pattern, harboring Plasmid DNA are an indication of risk to human health in the communities around Manzala Lake, from such bacterial pathogens, which live in polluted and stressed environment.